Addressing Participation and Intellectual Disability: A Discourse Analysis of Rhetoric from Social Support Staff and Disability Sports Leaders - Eric Svanelöv; Jonas Stier; Per Enarsson; Eva Flygare Wallén; Lena Talman (Scandinavian Journal of Disability Research)
Intellectual disability is often discussed in terms of dependence, social support and participation. The right to participate is important in different social contexts; however, because of able-minded judgement there are diminished opportunities within these contexts for disabled people to experience social justice. How intellectual disability and participation are talked about (re)constructs discourses and affects individuals within these discourses. This study explored how staff and leaders talk about participation and intellectual disability. Ten social support services staff and disability sports leaders were interviewed, and the interviews were analysed using discursive psychology. The study showed that intellectual disability is constructed through discourses of being (ab)normal and as an inconvenience for participation. These discourses diminish disabled people’s abilities, rendering participation powerless.